Canakinumab for the management of pyoderma gangrenosum: a case series of two patients and literature review - Howard Jie Yang; William Spratt; Francis Yi Xing Lai; Senhong Lee (Journal of Dermatological Treatment)
Aims To evaluate the efficacy and adverse events of canakinumab in the treatment of pyoderma gangrenosum (PG).Methods We report two cases of refractory PG treated with canakinumab after failing multiple therapies.Results A 44-year-old female achieved complete ulcer resolution after 31 months of canakinumab but experienced recurrent infections, including pneumonia requiring intensive care unit (ICU) admission. A 49-year-old male showed no improvement and suffered recurrent Pseudomonas infections, leading to treatment cessation after nine months.Conclusions We present a case series of two patients with PG on canakinumab therapy, both of whom experienced significant infections needing hospitalization. Further studies are needed to evaluate the efficacy and complication profile of canakinumab against other biologic therapy options.